46 DNACPR documentation & treatment escalation plans in elderly patients with a neck of femur fracture. (12th November 2018) - Evans, David; Bowen, Megan; Fowler, Tim
Abstract : Aim: To improve the documentation of DNACPR decisions and Treatment Escalation Plans (TEPs) in elderly patients (>75 year) presenting with a neck of femur fracture. Methods: Initial Audit (January 2018) + Re audit (March 2018) Inclusion Criteria: 20 consecutive patients over the age of 75 years, presenting with a neck of femur fracture (AO–31 A–C) To assess: Was a DNACPR decision made during the admission? Was discussion of this decision with the patient documented in the medical notes? Was discussion with the NOK documented in the medical notes? Was the DNACPR form countersigned by the responsible orthopaedic/orthogeriatric consultant? Was a TEP clearly documented in the medical notes? AMTS, ASA and PRISMA7 score to assess frailty Interventions: Staff education sessions (junior doctors + nursing staff) Improved availability of DNACPR and treatment escalation plan paperwork Posters within the doctors' office Results: Comparison of the two audit cycles shows an improvement in all aspects measured. The percentage of a documented DNACPR decision increased from 40% to 70%, and in the re-audit 100% of DNACPR forms were countersigned by a consultant. TEPs were also seen to increase by 100% in the re-audit. Conclusion: Fractured neck of femur has a high mortality rate. Therefore these discussions should be had early, ideally on admission and prior to surgery. As such, we have targeted our interventions towards reminding the admitting doctor, when appropriate, to have the resuscitation conversations. We acknowledge that it is not appropriate for every patient with a fractured neck of femur to have a DNACPR form signed, and as such we have concentrated on improving the documentation of DNACPR decisions, rather than the proportion of DNACPR forms signed. The staff education sessions, the improved availability of DNACPR paperwork and visual reminders around the doctors' office clearly improved the documentation of DNACPR decisions.